Short-and Long-Term Expression of Vegf: A Temporal Regulation of a Key Factor in Diabetic Retinopathy - Bucolo, Claudio; Barbieri, Annalisa; Viganò, Ilaria; Marchesi, Nicoletta; Bandello, Francesco; Drago, Filippo; Govoni, Stefano; Zerbini, Gianpaolo; Pascale, Alessia (Frontiers in Pharmacology, 2021)
To investigate the role of VEGF at different phases of diabetic retinopathy (DR), we assessed the retinal protein expression of VEGF, HIF-1α and PKCβ/HuR pathway in Ins2Akita (diabetic) mice at different ages. We used C57BL6J mice (WT) at different ages as control. Retina status, in terms of tissue morphology and neovascularization, was monitored in vivo at different time points by optical coherence tomography (OCT) and fluorescein angiography (FA), respectively. The results showed that VEGF protein expression increased along time to become significantly elevated (p<0.05) at 9 and 46 weeks of age compared to WT mice. The HIF-1α protein level was significantly (p<0.05) increased at 9 weeks of age while PKCβII and HuR protein levels were increased at 46 weeks of age compared to WT mice. The thickness of retinal nerve fiber layer as measured by OCT was increased at 9 and 46 weeks of age, while no difference in the retinal vessels were observed by FA. The present findings show that the retina of the diabetic Ins2Akita mice, as expected for mice, does not develops proliferative retinopathy even after 46 weeks. However, diabetic Ins2Akita mice recapitulate the same evolution of patients with DR in terms of both retinal neurodegeneration and pro-angiogenic shift, this latter indicated by short and long-term VEGF expression. The different time-dependent VEGF expression in the retina of diabetic Ins2Akita mice is associated to its regulation via HIF-1α or PKCβII/HuR pathway. In conclusion, these data seem to suggest that pharmacological intervention in DR might be chosen, among other reasons, on the basis of the specific stages of the pathology in order to obtain the best clinical outcome.